1972
DOI: 10.1039/f19726800749
|View full text |Cite
|
Sign up to set email alerts
|

Some experimental factors which govern the potential of the palladium hydride electrode at 25 to 195°C

Abstract: A purpose of this paper is to present some of the experimental electrochemical properties of the palladium hydride electrode that have been found between 25 and 200°C. The electrode potentials of palladium hydride were studied in aqueous solutions of sodium hydroxide and hydrochloric acid, in the presence and absence of carbon dioxide and nitrogen. All potentials are measured with respect to a platinum-hydrogen electrode. Use of relative resistance is made to establish the hydrogenpalladium composition and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…Previously, both palladium hydride (1,(9)(10)(11)(12)(13) and platinized (or palladized) platinum hydrogen electrodes (2-7) have been employed for this purpose. However, both electrodes suffer from a number of problems that may prevent their use in specific systems.…”
mentioning
confidence: 99%
“…Previously, both palladium hydride (1,(9)(10)(11)(12)(13) and platinized (or palladized) platinum hydrogen electrodes (2-7) have been employed for this purpose. However, both electrodes suffer from a number of problems that may prevent their use in specific systems.…”
mentioning
confidence: 99%
“…The phase diagram for the palladium hydrogen system has been extensively studied by many workers (9)(10)(11)(12)(13)(14)(15)(16), and the average of their data is shown in Fig. 7 together with the diffusion coefficients for hydrogen in ~ -0.9 …”
Section: Resultsmentioning
confidence: 99%
“…Many metal ions and anions are stable in hydrogenated systems and hydrogen electrodes have been shown to function at elevated temperatures. However, the problems involved with these electrodes are the precise determination of hydrogen fugacity and the difficulty of application for in situ pH measurements.The potential decay of palladium-hydride electrodes has been used for the measurement of pH in high temperature aqueous systems by a number of workers (1,(9)(10)(11)(12). The work of Dobson and co-workers (9-12) on this system has indicated that palladium-hydride electrodes exhibit Nernstian responses up to 195~ However, their work was restricted to highly acidic or basic solutions, and no data were obtained for the technologically important pH range from 5 to 13.…”
mentioning
confidence: 99%
“…For example, Dobson et al [61][62][63], Macdonald and coworkers [7,64,65], and nagy and Yonco [66] explored the palladium/hydrogen system as a reference electrode, as well as a pH indicator electrode. The work by Dobson et al [61][62][63] and Macdonald © Woodhead Publishing Limited, 2012 [7,64,65] used palladium wire or palladized platinum electrodes that had been cathodically charged into the b region of the Pd-H phase diagram, where solid palladium hydrides are formed ( Fig. 11.12).…”
Section: Other Internal Reference Electrodesmentioning
confidence: 99%
“…a variety of sensors have been developed to measure the activity of H + in high temperature aqueous solutions, including Pd/H electrodes [61][62][63][64], Pt/ H 2 electrodes [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], metal/metal oxide electrodes [80,81], glass electrodes [82], and most importantly yttria-stabilized zirconia [Zro 2 (Y 2 o 3 )] electrodes [44,[71][72][73]. The latter [Zro 2 (Y 2 o 3 )] sensors have now been used for monitoring pH in supercritical systems at temperatures to 528°c [73], which is more than 150°c higher than the critical temperature.…”
Section: Ph Sensorsmentioning
confidence: 99%